KUAT TEKAN PADA CAMPURAN BETON DENGAN BAKTERI YANG DIINOKULASI DAN LIMBAH BENDA UJI - Rayhan Asy Syukri, Muhammad; Maharani, Wulan; Muhammad Mauludin, Luthfi; Karnisah, Iin; Petrus Krisologus, Yulianto (Direktorat Bina Teknik Jalan dan Jembatan, 2025)
Concrete is a material commonly used as road and bridge structure and is very prone to cracking in hard-to-reach areas. Innovation in the form of self-healing concrete (SHC) can repair its cracks. Meanwhile, concrete waste remains a challenge that needs to be addressed and utilized to reduce the reliance on natural materials. This study utilises Bacillus megaterium bacteria as a self-healing agent and concrete waste as a substitute for coarse aggregate applied in regular concrete (20 MPa) with a mix design based on ACI 211.1-91. Variations in bacterial content are 2% and 4% of the weight of water, and variations in concrete waste are 25%, 50%, and 75% of the weight of coarse aggregate with a substitution of 10% fly ash and 2% calcium lactate of the weight of cement. The results showed an increase in compressive strength of 5.39% from 21.5 MPa for waste concrete to 20.4 MPa but a decrease of 0.46% from 21.6 MPa for regular concrete. Then, the bacteria showed self-healing or covered the cracks on the seventh day after testing. Additionally, the bacteria were able to restore the strength of the concrete by 80.22% to 99.19% after retesting on the 28th day. Therefore, concrete with bacteria based on concrete waste has the potential to be applied to road and bridge construction. Kata Kunci: bacillus megaterium, beton normal, kuat tekan, limbah beton, self-healing concrete. Keywords: bacillus megaterium, compressive strength, regular concrete, self-healing concrete, waste concrete